Symptomatic Primary (AL) Amyloidosis of the Stomach and Duodenum - Reidar Fossmark; Espen Skarsvåg; Harald Aarset; Henrik Hjorth-Hansen; Helge L. Waldum (Case Reports in Gastrointestinal Medicine)
Primary (AL) amyloidosis of the gastrointestinal tract is relatively rare, and symptomatic amyloidosis of the stomach is even more seldom. We present the case of a patient who was referred to upper endoscopy because of weight loss, nausea, and vomiting. Large areas of intramucosal hemorrhages were seen, and biopsies resulted in profuse bleeding stopped with endoscopic clips. The biopsies showed amyloid depositions and further workup revealed that the patient also had cardiac and neuropathic involvements. The patient started treatment with dexamethasone, melphalan and bortezomib. After treatment was started the nausea and epigastric discomfort improved, and a reduction in the biochemical markers troponin T, NT-proBNP, and M-component was observed. Gastric amyloidosis is rarely seen at upper endoscopy in patients without a previously established diagnosis, but the unusual endoscopic findings and bleeding tendency after biopsy should be kept in mind by gastroenterologists.